The One Million Cisterns Programme—a viability assessment of community rainwater management in Brazil - Cardoso Castro, Pedro Pablo; Vachkova, Maya; Ravena, Nirvia; Veloso, Nircele (Frontiers in Sustainability, 2024)
This research investigated the governance of the national community-based rainwater harvesting initiative, known as One Million Cisterns (P1MC), within the local context of the Brazilian Amazon rainforest. The initiative aimed to empower communities by providing water collection infrastructures and involved over 3,000 civil society organisations and various local and national bodies. Our study observed that while some communities thrived, others faced challenges in adopting and maintaining the cisterns. Focusing on communities near the city of Belém, Pará, within a specific Protected Extractivist Reserve Areas (RESEX), we explored the factors behind success and failure in managing rainwater systems. By applying Ostrom’s Institutional Analysis and Development Framework (IADF) and Beer’s Viable System Model (VSM), we assessed local institutional arrangements and community self-organisation. Through questionnaires and interviews with 109 end-users between 2018 and 2022, we identified two distinct organisational structures and their associated pathologies. The combined use of IADF and VSM provided valuable insights into the structural and institutional dynamics affecting system adoption, maintenance, and governance. Our findings emphasise the importance of a comprehensive framework integrating these analytical tools for designing effective social programs in Brazil. This study contributes to the ongoing discourse on sustainable development and resource management in the Amazon region, highlighting the significance of tailored governance structures and community engagement in addressing complex environmental challenges.